2022
DOI: 10.1007/s43032-021-00822-w
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Signatures of Cortisol in First Trimester Small-for-Gestational Age

Abstract: Background: Abnormal maternal hypothalamus-pituitary-adrenal axis is associated with fetal growth, and we hypothesized that the alteration in metabolic signatures of cortisol might be detectable during early pregnancy. The objective of this study was to identify predictable maternal serum signatures of cortisol metabolism during the rst trimester of women who are expected to deliver small-for-gestational age (SGA) neonates.Methods: This prospective cohort study included 112 pregnant women (with and without SGA… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…The consequence of this process leads to increased fetal calorie consumption. 6 Some studies outlined that maternal cortisol levels affect fetal development, such as the effect on fetal weightfor-age development in the first trimester 7 and the third-trimester cortisol levels related to an increase in neonatal adiposity up to 1-6 months postpartum. 8 A study by Braithwaite et al of 1233 first-time mothers (96.1% White British) at 32 weeks gestation found that maternal cortisol levels were positively related to male infant' postpartum weight with β of 0.167 and p of 0.036 9 .…”
Section: Introductionmentioning
confidence: 99%
“…The consequence of this process leads to increased fetal calorie consumption. 6 Some studies outlined that maternal cortisol levels affect fetal development, such as the effect on fetal weightfor-age development in the first trimester 7 and the third-trimester cortisol levels related to an increase in neonatal adiposity up to 1-6 months postpartum. 8 A study by Braithwaite et al of 1233 first-time mothers (96.1% White British) at 32 weeks gestation found that maternal cortisol levels were positively related to male infant' postpartum weight with β of 0.167 and p of 0.036 9 .…”
Section: Introductionmentioning
confidence: 99%